Facing the rising sun: Political imagination in Black adolescents’ sociopolitical development - Scott, Edward D.; Harris, Johari; Smith, Chauncey D.; Ross, Latisha (Frontiers in Psychology, 2023)
Black adolescents occupy one of the most precarious and marginalized social locations of society, yet they remain vigilant against oppression. Indeed, Black youth have a vast history of political action and activism around domestic and global issues. Existing scholarship frequently examines the sociocultural and cognitive factors associated with Black adolescents' political and civic engagement and related outcomes. Lost in these interrogations is an examination of the psychological processes that undergird adolescents’ sociopolitical visions. To address this gap, this conceptual analysis examines political imagination and its role in Black adolescents’ sociopolitical development. Political imagination is the cognitive space and process where people consciously distance the present moment to engage, explore, examine, and (de)construct sociopolitical worlds or realities.